PERAN RUANG BELAJAR POSKO KKN DALAM MENINGKATKAN MINAT BELAJAR SISWA DI DESA BULU-BULU - Andi Tabrani Rasyid; Wahyu Ramadhan, Alpinalisa, Lisa; Nirma lasari, Nu- raeni, Asmidar; Azisah Nurul Ilmi A.K, Herman , Sahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the role of the post study room implemented by KKN students in increasing student interest in learning in Bulu-Bulu Village. The re- search method used a qualitative approach with observation, interviews, and doc- umentation techniques. The research subjects consisted of elementary and middle school students, KKN students as facilitators, and parents of students. The results showed that the post study room had a positive influence on students' motivation and interest in learning, through interactive teaching methods, emotional support, and role models from the facilitators. However, there were still obstacles such as limited facilities and study hours that sometimes clashed with other student activi- ties. The conclusion states that the post study room is very helpful in increasing interest in learning, provided it is equipped with good resource support and coordi- nation.